1998
DOI: 10.1001/archotol.124.8.871
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Gastrostomy Tubes in Patients Undergoing Intensive Irradiation for Cancer of the Head and Neck

Abstract: The use of PGTs significantly reduces weight loss and the rate of hospitalization for dehydration and complications of mucositis. Treatment interruptions may also be avoided by the use of PGTs in patients with good performance status. We encourage patients scheduled for intensive radiation therapy to receive a PGT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
179
0
11

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(204 citation statements)
references
References 30 publications
14
179
0
11
Order By: Relevance
“…Concerning treatment toxicity, we found that there were no haematological and renal toxicity differences between the PPEG and non-PPEG groups, which were similar to findings of other PPEG studies in other head and neck cancers (Lee et al, 1998;Assenat et al, 2011). However the effect of PPEG on patient's potassium status was different between the groups.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Concerning treatment toxicity, we found that there were no haematological and renal toxicity differences between the PPEG and non-PPEG groups, which were similar to findings of other PPEG studies in other head and neck cancers (Lee et al, 1998;Assenat et al, 2011). However the effect of PPEG on patient's potassium status was different between the groups.…”
Section: Discussionsupporting
confidence: 87%
“…Nourishment can be undertaken via percutaneous endoscopic gastrostomy and inserting the feeding tube to the stomach through the abdominal wall before radiation, called "prophylactic percutaneous endoscopic gastrostomy" (PPEG). PPEG has been effective in the maintenance of weight, reduced set-up error, reduced hospitalisation, reduced treatment interruption and improved quality of life (Lee et al, 1998;Chang et al, 2009;Mercuri et al, 2009;Salas et al, 2009;Chen et al, 2010;Assenat et al, 2011;Silander et al, 2011).…”
Section: Comparison Of Treatment Compliance and Nutritional Outcomes mentioning
confidence: 99%
“…Prior studies have shown that if these patients are not supplemented, they will likely experience severe dehydration, treatment intolerance, or severe treatment related complications that require hospitalization. 3, 4 Inherently, the surgical treatment of head and neck malignancies can be quite debilitating and result in significant mastication and deglutination dysfunction. [5][6][7] At times this involves radical resections that require complex reconstructions to maintain oropharyngeal continuity; and adjuvant radiation and/or chemotherapy may be required to maximize local control.…”
Section: Introductionmentioning
confidence: 99%
“…Groups have identified some factors that are predictive of a need for enteral support. 3,4,[14][15][16][17] One factor that has been clearly established is radiation therapy, particular when given postoperatively. 3,4,17 Other factors such as Stage IV disease, base of tongue tumor location, and heavy alcohol ingestion are less clearly defined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation